Application of Microwave Heating in Biomass Hydrolysis and Pretreatment for Ethanol Production - Euis Hermiati; Djumali Mangunwidjaja; Ttiti C Sunarti; Ono Suparno; Bambang Prasetya (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Recently, due to depletion of fossil derived energy stock in the world, there are growing interests in utilizing biomass sources of bioethanol. There are basically two types of biomass that are usually used or converted to ethanol, starchy and lignocellulosic biomass. The conversion of starchy and lignocellulosic materials are widely explored, however, there are still some drawbacks, such as high enzyme cost and intensive energy needed. Therefore, lower cost as well as energy and time efficient process technology in biomass conversion to ethanol is important in enhancing the use of biomass to substitute fossil fuel. Microwave heating offers some advantages to overcome these drawbacks, especially due to its quick heat transfer and its heating selectivity. In conventional heating the heat was transferred through conduction or convection process which took longer time. Thus, by using microwave, degradation of starchy and lignocellulosic biomass could be completed in shorter time than by using conventional heating method. The roles of microwave heating in the degradation of biomass, especially starchy and lignocellulosic biomass and its relation to the hydrolysis and pretreatment of that particular biomass for ethanol production are reviewed and discussed. Keywords: biomass, pretreatment, ethanol, microwave